New insights into physicochemical aspects involved in the formation of polyelectrolyte complexes based on chitosan and dextran sulfate. (1st November 2021) - Carvalho, Suzana Gonçalves; dos Santos, Aline Martins; Silvestre, Amanda Letícia Polli; Meneguin, Andréia Bagliotti; Ferreira, Leonardo Miziara Barboza; Chorilli, Marlus; Gremião, Maria Palmira Daflon
Abstract: Polyelectrolyte complexation is a technique based on interactions between polyelectrolytes of opposite charges driven by supramolecular interactions. Although many studies address the formation of polyelectrolyte complexes (PECs), few explore strategies and tools to select the best working conditions and are often based on empirical choices. This study evaluates the influence of pH, molecular weight, and polymeric proportion on the formation of PECs based on chitosan:dextran sulfate. In addition, it assesses the approaches that study the influence of pH on the zeta potential of polymeric dispersions as a tool in the design of PECs. Results showed that nanoparticles with an excess of polycation formed aggregates, while an excess of dextran sulfate reduced the size of the particles. The graph of zeta potential as a function of pH proved to be a promising tool in the choice of polymers and a better pH condition in the development of PECs. Graphical abstract: Unlabelled Image Highlights: CS-DS nanoparticles were prepared by the polyelectrolyte complexation method. The influence of pH, molecular weight and proportion of polymers on the formation of polyelectrolyte complexes was evaluated. The study of ZP as a function of pH can assist in the choice of polymers and the best pH conditions of the reaction medium.